Analysis of Investment Functions in Central Java - Anjarbanu, Bimo Cendekiarto; Firmansyah, Firmansyah (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2023)
This study aims to analyze the factors that influence investment in Central Java. These factors consist of interest rates, inflation, and GRDP. This study uses time series data from 1990-2021. Source of data used in this research is secondary data. The analytical method used in this study is multiple regression analysis (OLS) with the Partial Adjustment Model (PAM) method and the programming used to analyze the data in this study is the Eviews 10 and SPSS 21 applications. The results obtained from this study are that interest rates in the short term and long term have a negative and significant effect on investment in Central Java. Inflation in the short term and long term has a positive and insignificant effect on investment in Central Java. GRDP in the short and long term has a negative and significant effect on investment in Central Java. Interest rates, inflation and GRDP simultaneously have a significant effect on investment in Central Java.